2015
DOI: 10.1039/c5cp02247a
|View full text |Cite
|
Sign up to set email alerts
|

Direct measurements of the interactions between clathrate hydrate particles and water droplets

Abstract: Clathrate hydrate particle agglomeration is often considered to be one of the key limiting factors in plug formation. The hydrate particle-water interaction can play a critical role in describing hydrate agglomeration, yet is severely underexplored. Therefore, this work investigates the interactions between water droplets and cyclopentane hydrate particles using a micromechanical force (MMF) apparatus. Specifically, the effect of contact time, temperature/subcooling, contact area, and the addition of Sorbitane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 29 publications
1
54
1
Order By: Relevance
“…This occurs because the droplet is forced to change its shape at the last stages of coalescence, which is consistent with the interpretation of experimental data. 55 Qualitatively, the features just described are common in all simulated force -distance profiles obtained for the bare or the coated droplets, although different surfactants are considered. Some differences are however observed.…”
Section: A Hydrate Particle -Droplet Coalescencementioning
confidence: 88%
See 1 more Smart Citation
“…This occurs because the droplet is forced to change its shape at the last stages of coalescence, which is consistent with the interpretation of experimental data. 55 Qualitatively, the features just described are common in all simulated force -distance profiles obtained for the bare or the coated droplets, although different surfactants are considered. Some differences are however observed.…”
Section: A Hydrate Particle -Droplet Coalescencementioning
confidence: 88%
“…Long-range corrections to electrostatic interactions were treated using the Particle Mesh Ewald (PME) method. 47 The simulated temperature was maintained at We conducted steered MD simulations to mimic the hydrate coalescence as investigated by recent experimental approaches; [51][52][53][54][55] in our simulations the droplet was pulled towards the hydrate particle, which was maintained fixed. We used a harmonic spring with a force constant of 3000 kJ/mol.nm 2 tethered to the center of mass (COM) of the droplet.…”
Section: Simulation Methodologymentioning
confidence: 99%
“…Span 80 has a hydrophilic-lipophilic balance (HLB) value of 4.3, which is considered as an oil soluble surfactant that can promote the formation of water-in-oil emulsion. Span 80 has been used as a hydrate anti-agglomerant in labroratory researches [19,20]. In this study, the synergistic effect between AA and Span 80 is observed.…”
Section: Performance Of Compounded Anti-agglomerantsmentioning
confidence: 71%
“…5,6 In some cases, the amount and type of hydrate accumulation may lead to a blockage that completely disrupts flow. [7][8][9] These blockages are not only costly and hazardous to remove, but also lead to significant losses in production due to downtime. Thus, gas hydrate is considered the major flow assurance challenge in the production of oil and gas.…”
Section: Introductionmentioning
confidence: 99%